Nuclear calcium signalling in the regulation of brain function - Bading, Hilmar (Nature reviews. Neuroscience, 2013)
Nuclear calcium is an important mediator of activity-dependent gene expression in the nervous system. It serves as a signalling end point in synapse-to-nucleus communication and activates gene programmes needed for the long-term implementation of many neuroadaptations, including memory consolidation, acquired neuroprotection and the development of chronic pain. The requirement of nuclear calcium signals for long-term memory formation is evolutionarily conserved from flies to mammals.The mechanism through which synaptic activity leads to increases in the intranuclear calcium concentration involves stimulation of synaptic NMDA receptors, generation of backpropagating action potentials and the opening of voltage-gated calcium channels. Nuclear calcium transients may also be initiated or enhanced by calcium release from intracellular calcium stores mediated by inositol triphosphate or ryanodine receptors.Nuclear calcium is one of the most potent regulators of gene expression. It controls the activity or nuclear localization of several transcriptional regulators (which include CREB (cyclic AMP-responsive element-binding protein), CBP (CREB-binding protein), class IIa HDACs (histone deactylases) and MECP2 (metyhyl-CpG-binding protein 2)) that either generate or interpret chromatin modifications.The target gene pool of nuclear calcium signalling comprises nearly 200 genes that function, for example, in the regulation of dendrite architecture and spine density and shape. The neuroprotective activity of nuclear calcium signalling appears to be mediated by a set of genes that render mitochondria more resistant to harmful conditions.The effects of nuclear calcium on gene regulation and neuroprotection are antagonized by the stimulation of extrasynaptic NMDA receptors that trigger transcriptional shut-off and cell death pathways.Dysfunctioning of nuclear calcium signalling, referred to as 'nuclear calciopathy', may be a common factor in the aetiology of neurodegenerative and neuropsychiatric conditions. The modulation of nuclear calcium signalling may be a novel therapeutic strategy for the treatment of neurological disorders.